Potential of Stenotrophomonas maltophilia in green biosurfactant production - Ferreira, Isabela Natália da Silva; Takaki, Galba Maria Campos (Seven Editora, 2023)
The literature describes several studies focused on the application of S. maltophilia in different areas of biotechnology. Due to its ease of interaction with numerous environments and living beings, this bacterium has an excellent adaptability, being able to convert different substrates into products of high environmental and technological interest. Stenotrophomonas maltophilia is a gram-negative, aerobic, ubiquitous, rod-shaped bacterium belonging to the class of gammaproteobacteria and can be found in various natural and anthropogenic environments, e.g. soil, water, sediments or in association with plants. Biosurfactants are an alternative, compatible with the environment, for the use of chemically synthesized surfactants, since it is a bioproduct obtained through the metabolism of microorganisms and plants. Like their synthetic counterparts, biosurfactants comprise a wide variety of chemical structures and also excellent surfactant properties. The literature presents a wide range of studies focused on the production of biosurfactant by S. maltophilia using several substrates, temperature conditions, pH, salinade and fermentation times. In addition, there is also a huge variety of application of these biosurfactants produced, which drives the incentive to study this microorganism in the production of biosurfactants. DOI: https://doi.org/10.56238/alookdevelopv1-147